2008
DOI: 10.1016/j.bandl.2008.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral capacity for speech sound processing in auditory comprehension: Evidence from Wada procedures

Abstract: Data from lesion studies suggests that the ability to perceive speech sounds, as measured by auditory comprehension tasks, is supported by temporal lobe systems in both the left and right hemisphere. For example, patients with left temporal lobe damage and auditory comprehension deficits (i.e., Wernicke's aphasics), nonetheless comprehend isolated words better than one would expect if their speech perception system had been largely destroyed (70-80% accuracy). Further, when comprehension fails in such patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
72
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 16 publications
5
72
0
Order By: Relevance
“…The former assesses the stage prior to word-form recognition ( i.e ., phoneme recognition) while the latter assesses phrase comprehension, which includes semantic and syntactic processing. More refined methods (Miglioretti & Boatman, 2003; Hickok et al , 2008; Goll et al , 2010; Rogalski et al , 2011; Bormann & Weiller, 2012; Thothathiri, Kimberg & Schwartz, 2012) will be required in future investigations for the specific evaluation of auditory word-form recognition. It should be noted, however, that resection of sites implicated in auditory sentence comprehension by electrical interference does increase the incidence of post-operative impairment in auditory comprehension (Hamberger et al , 2005).…”
Section: Causal Involvement Of Anterior Stg In Word Recognitionmentioning
confidence: 99%
“…The former assesses the stage prior to word-form recognition ( i.e ., phoneme recognition) while the latter assesses phrase comprehension, which includes semantic and syntactic processing. More refined methods (Miglioretti & Boatman, 2003; Hickok et al , 2008; Goll et al , 2010; Rogalski et al , 2011; Bormann & Weiller, 2012; Thothathiri, Kimberg & Schwartz, 2012) will be required in future investigations for the specific evaluation of auditory word-form recognition. It should be noted, however, that resection of sites implicated in auditory sentence comprehension by electrical interference does increase the incidence of post-operative impairment in auditory comprehension (Hamberger et al , 2005).…”
Section: Causal Involvement Of Anterior Stg In Word Recognitionmentioning
confidence: 99%
“…On one hand, there is ample evidence that the motor system activates during speech perception (Fadiga, Craighero, Buccino, & Rizzolatti, 2002; Hickok, Buchsbaum, Humphries, & Muftuler, 2003; Wilson, Saygin, Sereno, & Iacoboni, 2004) and that disruption of motor function can, in some cases, result in changes in performance on some tasks (D’Ausilio et al, 2009; Grossman et al, 2008; Meister et al, 2007; Mottonen & Watkins, 2009; Schomers, Kirilina, Weigand, Bajbouj, & Pulvermuller, 2014; Tranel, Kemmerer, Adolphs, Damasio, & Damasio, 2003). On the other hand, there is compelling evidence that the basic ability to perceive and understand speech is not substantially affected by chronic damage to motor speech systems (Hickok, Costanzo, Capasso, & Miceli, 2011; Rogalsky, Love, Driscoll, Anderson, & Hickok, 2011), acute and complete deactivation of motor speech ability (Hickok et al, 2008), or the failure to develop articulate speech (Bishop, Brown, & Robson, 1990). …”
mentioning
confidence: 99%
“…In a striking demonstration of redundancy in the brain regions supporting speech perception, Hickok and colleagues reported that in patients undergoing the Wada procedure, the right hemisphere alone made fewer than 10% phonemic errors[3]. This apparent redundancy limits the extent to which speech perception deficits can be observed when any single region, such as speech motor cortex, is damaged.…”
mentioning
confidence: 99%